Role of mtDNA disturbances in the pathogenesis of Alzheimer's and Parkinson's disease - Antonyová, Veronika; Kejík, Zdeněk; Brogyányi, Tereza; Kaplánek, Robert; Pajková, Martina; Talianová, Veronika; Hromádka, Róbert; Masařík, Michal; Sýkora, David; Mikšátková, Lucie; Martásek, Pavel; Jakubek, Milan (DNA repair, 2020)
Neurodegenerative diseases (e.g. Alzheimer's and Parkinson's disease) are becoming increasingly problematic to healthcare systems. Therefore, their underlying mechanisms are trending topics of study in medicinal research. Numerous studies have evidenced a strong association between mitochondrial DNA disturbances (e.g. oxidative damage, mutations, and methylation shifts) and the initiation and progression of neurodegenerative diseases. Therefore, this review discusses the risk and development of neurodegenerative diseases in terms of disturbances in mitochondrial DNA and as a part of a complex ecosystem that includes other important mechanisms (e.g. neuroinflammation and the misfolding and aggregation of amyloid-β peptides, α-synuclein, and tau proteins). In addition, the influence of individual mitochondrial DNA haplogroups on the risk and development of neurodegenerative diseases is also described and discussed.
Keywords: alpha-Synuclein; Humans; mitochondriální DNA; Oxidative stress; Neuroinflammation; DNA, Mitochondrial; mutace; Protein Aggregation, Pathological; tau Proteins; Mitochondrial DNA disturbances; Inflammation; lidé; Alzheimer Disease; Alzheimer’s disease; Alzheimerova nemoc; amyloidní beta-protein; zánět; proteiny tau; Parkinson’s disease; patologická konformace proteinů; alfa-synuklein; Amyloid beta-Peptides; poškození DNA; DNA Damage; Peptide and protein aggregation; Mutation; Parkinson Disease; Parkinsonova nemoc